Kajian Hermeneutika Wilhem Dilthey pada Lagu Celengan Rindu - Rosmini Madeamin (Lembaga Pengembangan Kinerja Dosen, 2024)
the aim of this research is to describe the meaning contained in the lyrics of the song celengan rindu by fiersa besari through the analysis of erlebnis, ausdruck, and verstehen of wilhelm dilthey's hermeneutical study. This type of research is descriptive using a qualitative research design. The data from this research are the lyrics of the song celengan rindu by fiersa besari. The theory that is the basis of this research uses wilhem dilthey's hermeneutics which focuses on three concepts, namely erlebnis (lived experience), ausdruck (expression), and verstehen (understanding). The data analysis technique used in this research is descriptive qualitative. The data were analyzed using listening, note-taking and documentation techniques. The results of this research using wilhem dilthey's hermeneutics show (1) the erlebnis concept includes: (a) fiersa besari's life experience (b) the history of the song celengan rindu as viewed from fiersa besari's life experience. (2) the concept of ausdruck in this song is fiersa besari's expression about long distance relationships. (3) the verstehen concept includes: (a) long distance relationships described by fiersa besari through the song piggy bank rindu (b) excessive jealousy that can occur in long distance relationships described by fiersa besari through the song piggy bank rindu.